3Y-TZP/Ta Biocermet as a Dental Material: An Analysis of the In Vitro Adherence of Streptococcus Oralis Biofilm and an In Vivo Pilot Study in Dogs - Anton Smirnov; Oleg Yanushevich; Natella Krikheli; Nestor Washington Solis Pinargote; Pavel Peretyagin; Sergey Grigoriev; Luis Alou; David Sevillano; Roberto López-Piriz; Francisco Guitian; José Florindo Bartolomé (Antibiotics, 2024)
The surface adhesion of bacterial cells and the in vivo biocompatibility of a new ceramic–metal composite made of zirconium dioxide and tantalum were evaluated. Within the framework of an in vitro study using the crystal violet staining and colony counting methods, a relatively similar adhesion of Streptococcus oralis to the 3Y-TZP/Ta biocermet (roughness Ra = 0.12 ± 0.04 µm) and Ti-Al6-V4 titanium alloy (Ra = 0.04 ± 0.01 µm) was found. In addition, in an in vivo preliminary study focused on the histological analysis of a series of rods implanted in the jaws of beagle dogs for a six-month period, the absence of any fibrous tissue or inflammatory reaction at the interface between the implanted 3Y-TZP/Ta biocermets and the new bone was found. Thus, it can be concluded that the developed ceramic–metal biocomposite may be a promising new material for use in dentistry.